An Evocative Translation and Theology of the Hebrew לְרוּחַ הַיּוֹםin Genesis 3:8 - Henry Sitanggang (Jurnal Koinonia, 2022)
This study has examined the Hebrew expression לְרוּחַ הַיּוֹם, "in the cool of the day" (NASB), to determine the correct translation, motif, and theology on the ground of the context. By the exegetical framework, the literary context and structure portray the discourse of the imminent judgment of God and the repercussion. The proposed translation because of the Spirit of the day adduces the motif of divine judgment with God appearing in theophany, the glory-Spirit presence. The particle לְ supports the causative motif (because) instead of the preposition in. The theophany, the voice of God, judicially provokes the first humans to appear sinful before God and receive divine remedy for their sin. In conclusion, the text foreshadows the eschatological hope of the coming Lord as Judge in the great day of judgment and hope for salvation.